2015
DOI: 10.19168/jyu.55431
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis of the Relationship between Macroeconomic Factors and the Stock Market Returns in Pakistan

Abstract: Abstract:The purpose of this research is to investigate the relationship between Karachi stock market 100 index and macroeconomic variables, i.e., inflation, industrial production, money supply, exchange rate and interest rate. The long term relationship between macroeconomic variables and stock market returns has been analyzed by using Johnson Cointegration test, Augmented Dicky Fuller (ADF) and Phillip Perron (PP) tests. The Autoregressive Conditional heteroskedasticity Lagrange Multiplier (ARCH LM) test pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
4
15
2
2
Order By: Relevance
“…Linear regression revealed t value less than 1.96 furthermore p numeric larger to 0.05 suggesting no statistical relationship between KSE returns and inflation rate during the low inflationary period. Present findings support earlier works; Ullah et al (2014); Zaheer and Rashid (2014); Rafay et al (2014) and reject the attempts of; Sarwar et al (2014);Iqbal et al (2013); Sohail and Zakir (2011). Vol.…”
Section: Resultssupporting
confidence: 91%
“…Linear regression revealed t value less than 1.96 furthermore p numeric larger to 0.05 suggesting no statistical relationship between KSE returns and inflation rate during the low inflationary period. Present findings support earlier works; Ullah et al (2014); Zaheer and Rashid (2014); Rafay et al (2014) and reject the attempts of; Sarwar et al (2014);Iqbal et al (2013); Sohail and Zakir (2011). Vol.…”
Section: Resultssupporting
confidence: 91%
“…This means Inflation was found to have a negative impact on Stock returns in Singapore; accounting for about 9% of these returns. This finding was in line with expectations; as discussed earlier with regards to findings in Alam and Rashid (2014), as well as Chia and Lim (2015).…”
Section: Hypothesis 2: Monetary Supply Has a Positive Impact On Stisupporting
confidence: 93%
“…Money Supply was also found to only influence stock returns via Inflation. This ISSN 1946-052X 2017 study also noted that this market saw concentrated shareholdings, and with the lack of popularity in stock investments, there was little noted incentive for informational and operational efficiency, explaining its low liquidity (Alam and Rashid, 2014). Chia and Lim (2015) used an Autoregressive Distributed Lag (ARDL) Bounds Test to examine responses in the Malaysian Share Price Index to Industrial Production, Inflation, Monetary Supply, Interest rate and Exchange rate.…”
Section: Macroeconomy and Stock Returnsmentioning
confidence: 99%
“…It was also found that income and saving rate are correlated with stock market growth. Alam and Rashid [16] examined the relationship between Karachi stock market 100 index and macroeconomic variables, i.e., inflation, industrial production, money supply, exchange rate and interest rate. The long term relationship between macroeconomic variables and stock market returns has been analysed by using Johansen Cointegration test, Augmented Dicky Fuller (ADF) and Phillip Perron (PP) tests.…”
Section: Shrestha and Subedimentioning
confidence: 99%